Zinc-iodine battery diaphragm based on three-dimensional covalent organic framework as well as preparation method and application of zinc-iodine battery diaphragm
By using a three-dimensional co-price organic frame structure in zinc iodine batteries, it is difficult to achieve the problem of fast ZN2+transmission and effectively blocking i3-shuttle in traditional diaphragms, which significantly improves the performance and cycle life of the battery.
Patent Information
- Application Number
- CN202411420483.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-12
AI Technical Summary
It is difficult for traditional zinc-iodine battery separators to achieve rapid Zn2+ transmission and effectively block I3-shuttle, resulting in a degradation of battery performance.
The three-dimensional covalent-frame organizational diaphragm is adopted, and through the appropriate pore-diameter design (0.8nm) and static electricity, ZN2+can be allowed to quickly pass and effectively limit the shuttle of i3-.
It significantly improves the discharge capacity, circulation performance, Kulun efficiency and multiplier performance of zinc iodine batteries, and extend the cycle life of the battery.
Smart Images

Figure CN119381697A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a three-dimensional covalent organic framework zinc-iodine battery separator and a preparation method and application thereof. Background Art
[0002] Although the widespread use of traditional fossil energy has promoted rapid economic development, it has also caused many problems such as energy crisis and greenhouse effect, and a clean energy transition is needed. To this end, the country has put forward the strategic goals of "carbon peak" and "carbon neutrality". The development of green renewable energy such as solar energy, wind energy and hydropower is an important way to achieve these goals. However, due to environmental and geographical limitations, these renewable energy sources cause the power grid to be more volatile and difficult to use uninterruptedly, so it is necessary to develop more efficient energy storage technology.
[0003] Since the invention of lithium-ion batteries in 1990, they have been widely used in the fields of electronic products and new energy vehicles. This is mainly due to its advantages such as high energy density, high open circuit voltage and good cycle stability. However, the high cost of lithium-ion batteries and the safety issues of organic electrolytes such as flammability and thermal runaway have hindered their further development in the field of energy storage, especially in large-scale power stations. Although traditional lead-acid batteries have the advantages of low cost and good safety performance, their promotion and application in the field of energy storage are also limited due to their low volume energy density, poor cycle life and environmental pollution. Therefore, there is an urgent need to develop a new energy storage battery system with low cost, high safety and long life.
[0004] The positive electrode material of zinc-ion batteries has a crucial impact on performance. Currently, the mainstream research and development of metal oxides, metal sulfides, Prussian blue compounds and other positive electrode materials are mainly based on Zn 2+ Insertion / extraction mechanism stores charge. 2+ The large hydration radius and limited ion storage space provided by the positive electrode limit the power performance and energy density. Recently, the conversion reaction of halogen element positive electrodes has attracted much attention because of their high open circuit voltage, strong redox kinetics and excellent charge and discharge stability. Among them, halogen elements have higher boiling points and lower costs, and have greater development potential.
[0005] Zinc-iodine secondary batteries use an aqueous solution of dissolved zinc salts as the electrolyte, metallic zinc as the negative electrode, and elemental iodine as the positive electrode to store charge through a dissolution-deposition mechanism. Compared with batteries that use ion embedding or conversion reaction mechanisms, this type of battery has faster reaction speed, better reversibility, higher energy and power density, and has unique advantages such as safety, economy, environmental protection, and high efficiency. However, despite the relatively simple reaction mechanism, I3 -The intermediate products cause serious shuttle effects, which in turn affect the battery's performance indicators such as discharge capacity, Coulomb efficiency and cycle life.
[0006] The main reason for this problem is that the glass fiber separator widely used in traditional zinc-ion batteries has a large pore size (0.7-1.6 μm), which is difficult to effectively prevent the smaller size of I3 - The shuttling of ions makes it difficult to achieve high-performance zinc-iodine batteries. Although some ion-selective membranes (such as Nafion series membranes) can effectively inhibit I3 - However, its closed structure will reduce the Zn 2+ The conductivity of ZnO2 is low, which causes severe polarization in the battery and leads to a decrease in battery performance. Therefore, the key to solving this problem is to design an efficient separator that can ensure the conductivity of ZnO2. 2+ Pass quickly and effectively block I3 - The shuttle.
[0007] Recently, researchers have proposed a zeolite molecular sieve membrane with a smaller pore size (0.4 nm) to inhibit I3 - The shuttling of I3 can improve the performance indicators such as Coulombic efficiency, discharge capacity and cycle stability. Although zeolite molecular sieves can physically suppress I3 - However, the larger hydrated ions (0.43 nm) in the aqueous electrolyte limit its transmission efficiency. In addition, inorganic particles require additional binders to form a membrane, which makes it difficult to ensure the uniformity and continuity of the pore size. In addition, commercial iodine ion batteries are usually less than 25 μm thick, while the thickness of this zeolite molecular sieve membrane is 60 μm, which is not conducive to improving the volume energy density.
[0008] Therefore, developing a high I3 - Barrier efficiency and high Zn 2+ The integrated composite diaphragm with high transmittance to improve the discharge capacity, coulombic efficiency and rate performance of zinc-iodine batteries is one of the severe challenges currently facing this field. Summary of the invention
[0009] In order to solve the problem that zinc-iodine battery separators are difficult to achieve fast Zn 2+ Passing and effectively blocking I3 - To solve the problem of Zn-iodine battery shuttling, researchers proposed a new method for preparing zinc-iodine battery separators. This separator uses a three-dimensional organic framework structure (COFs) with a suitable pore size design, which can ensure that Zn 2+ Fast pass and block I3 -The conductive material in the separator can enhance the conductivity. The use of this separator can significantly improve the performance of zinc-iodine batteries, including discharge capacity, cycle performance, coulombic efficiency and rate performance.
[0010] At present, polyethylene and polypropylene separators widely used in lithium-ion batteries are difficult to be directly applied to zinc battery systems, mainly because they are non-hydrophilic and cannot wet aqueous zinc batteries, thus affecting the smooth flow of ion channels. When zinc-ion batteries were still in the research and development stage, the commonly used glass fiber separators showed good performance in positive electrodes such as oxides and sulfides, but it was difficult to achieve the ideal effect in zinc-iodine batteries.
[0011] To address these issues, we proposed a three-dimensional covalent organic framework material, which was prepared by the solvothermal reaction of tetraaminophenylmethane and terephthalaldehyde. It has a suitable pore size design (0.8nm), which allows Zn 2+ While passing quickly, micropore confinement and electrostatic effect can effectively limit I3 - Therefore, based on the above mechanism, the prepared three-dimensional composite covalent organic composite membrane can effectively inhibit the I3 - and greatly improve battery performance and cycle life.
[0012] To achieve the above object, the technical solution adopted by the present invention is:
[0013] A method for preparing a three-dimensional covalent organic framework zinc-iodine battery separator comprises the following steps:
[0014] (1) placing tetraaminophenylmethane and terephthalaldehyde ligand in an organic solvent and dispersing them by ultrasonication to obtain a homogeneous mixed solution;
[0015] (2) adding a catalyst to the mixed solution of step (1), heating the mixture to react, cooling the mixture after the reaction, filtering the mixture to obtain a solid powder, washing and purifying the solid powder, and drying the solid powder to obtain a highly crystalline three-dimensional covalent organic framework material;
[0016] (3) The highly crystalline three-dimensional covalent organic framework material prepared in step (2) and the conductive material are layered and assembled on the base membrane to obtain a three-dimensional covalent organic framework zinc-iodine battery membrane.
[0017] Furthermore, in step (1), the terephthalaldehyde ligand is one or more of 2-hydroxyterephthalaldehyde, 2.5-dihydroxyterephthalaldehyde, 2.5-diethoxyterephthalaldehyde, and 2.5-dimethoxyterephthalaldehyde.
[0018] Furthermore, in step (1), the molar ratio of the tetraaminophenylmethane to the terephthalaldehyde ligand is 1:1.5-2.5, preferably 1:2.
[0019] Furthermore, in step (1), the organic solvent is one or more of 1,4-dioxane, mesitylene, o-dichlorobenzene, and n-butanol. Preferably, the organic solvent is composed of 1,4-dioxane and mesitylene in a volume ratio of 1:1-4, and the specific ratio includes 1:1 or 1:4 or 3:7.
[0020] Furthermore, in step (1), the ultrasonic dispersion is carried out for 10 to 30 minutes at a temperature of 20 to 30°C.
[0021] Furthermore, in step (2), the catalyst is a 3-9 mol / L acetic acid solution, preferably a 3 mol / L acetic acid solution.
[0022] Furthermore, the volume ratio of the organic solvent to the catalyst is 3-5:0.1-0.2.
[0023] Furthermore, in step (2), the reaction temperature is heated to 90-120° C. and the reaction time is 70-90 h.
[0024] Furthermore, in step (2), the washing and purification uses a solvent of at least one of THF (tetrahydrofuran), methanol, ethyl acetate, and 1,4-dioxane.
[0025] Furthermore, in step (2), the drying is vacuum drying, the drying temperature is 90-130° C., and the drying time is 4-8 hours.
[0026] Furthermore, in step (3), the conductive material is one or more of graphene, Ketjen black, carbon black, and acetylene black.
[0027] Furthermore, in step (3), the pore size of the base membrane is 1-5 μm, and the base membrane is any one of glass fiber filter paper, polyethylene membrane, and polypropylene membrane.
[0028] Furthermore, step (3) specifically comprises the following steps: dispersing the organic framework material in ethanol, wherein the mass volume ratio of the organic framework material to the ethanol is 4-6 mg:30-50 ml, to obtain an organic framework material liquid; dispersing the conductive material in another portion of ethanol, wherein the mass volume ratio of the conductive material to the ethanol is 8-12 mg:30-50 ml, to obtain a conductive material liquid; wherein the mass ratio of the organic framework material to the conductive material is 4-6:8-12; and adopting a suction filtration method, sequentially suction-filtering the organic framework material liquid and the conductive material liquid onto a base diaphragm to prepare a zinc-iodine battery diaphragm.
[0029] Furthermore, the thickness of the zinc-iodine battery separator is 15-20 mm, and the natural thickness before assembly is 800-1000 μm. Preferably, the thickness of the zinc-iodine battery separator is 18 mm, and the natural thickness before assembly is 900 μm.
[0030] Furthermore, the tetraaminophenylmethane is replaced by adamantane.
[0031] A three-dimensional covalent organic framework zinc-iodine battery separator is prepared by any preparation method described in the present invention.
[0032] A zinc-iodine battery comprises a positive electrode, a negative electrode, an electrolyte and the battery separator of the present invention.
[0033] Furthermore, the positive electrode is made of carbon material, a binder is added, and a slurry is prepared, and then iodine is adsorbed to make the positive electrode, the carbon material is one or more of microporous carbon, coconut shell carbon or activated carbon, and the binder is one or more of polyvinylidene fluoride, polytetrafluoroethylene, and polyaniline;
[0034] The negative electrode is a negative electrode of metal zinc foil or other metal alloy containing zinc;
[0035] The electrolyte is a zinc salt aqueous solution, and the zinc salt includes zinc sulfate, zinc iodide, and zinc trifluoromethanesulfonate.
[0036] Furthermore, the electrolyte consists of 2-5 mol / L ZnSO4 and 0.1-0.3 mol / L ZnI2 aqueous solution.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention uses tetraaminophenylmethane and terephthalaldehyde ligands to react to form a covalent organic framework membrane, which has a suitable pore size design (0.8nm) and allows Zn 2+ While passing quickly, I3 can be effectively limited by aperture confinement and electrostatic effects. - Based on the above mechanism, the membrane can effectively inhibit the shuttling of I3 - It can shuttle and greatly improve the battery Coulombic efficiency, discharge capacity and cycle life.
[0039] (2) The amino or aldehyde group in the raw materials of the present invention is superior to the aldehyde or amine monomer containing sulfonate in the preparation method, and will have the advantage of "low cost" in actual production. At the same time, the assembled full battery is a zinc-iodine battery, which avoids the common positive electrode materials such as manganese dioxide, Prussian blue, and vanadium pentoxide that are easy to cause environmental pollution. In addition, the substrate used in the present invention is a glass fiber separator, which does not require complicated pre-treatment and preparation.
[0040] (3) Compared with the patents CN 115693022 B “a zinc-iodine battery separator based on a covalent organic framework, its preparation method and application” and CN 110534683 B “a lithium covalent organic framework nanosheet separator, its preparation and application”, the battery prepared by the present invention has better performance, for example, it can be used at a high current density (20 mA cm -2 ), can run stably for more than 800 cycles, further enhancing the performance of the full battery in actual production and life.
[0041] (4) In the prior art (e.g., CN 115693022 B, CN 110534683 B), the preparation of self-supporting membranes requires heating, evaporation and other processes, which are relatively complicated and the crystalline structure of the covalent organic framework is generally uneven, which is not conducive to ion conduction, especially the preparation of Li-based membranes, which is cumbersome and not conducive to large-scale production. The three-dimensional composite covalent organic composite membrane prepared by the present invention can quickly synthesize and expand different types of covalent organic frameworks. The entire process is convenient, simple, and fast, and has a more industrial application prospect.
[0042] (5) Compared with glass fiber separators and Nafion separators, the covalent organic framework separator prepared by the present invention is applied to zinc-iodine batteries and shows significantly improved discharge capacity, cycle performance, coulombic efficiency, rate performance and other indicators. Even after hundreds of high-current charge and discharge cycles, its capacity retention rate is high, far exceeding the indicators of some current zinc-based batteries and zinc-iodine batteries, thus showing great application prospects in energy storage secondary batteries.
[0043] (6) The three-dimensional covalent organic framework composite membrane prepared by the present invention adopts a one-step synthesis process, and the preparation method is simple, which is conducive to large-scale manufacturing. At the same time, the raw material cost is low and it has the characteristics of being environmentally friendly. In addition, the covalent organic framework material prepared by the Schiff base reaction is further assembled into a membrane with the advantage of being recyclable, and it can be dissolved in an acidic solution without polluting the environment.
[0044] (7) The zinc-iodine battery prepared using the three-dimensional covalent organic framework zinc-iodine battery separator of the present invention has wide applications in energy storage equipment, grid peak storage, low-speed electric vehicles, road lighting, port machinery, emergency power supply and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram of the structure of the three-dimensional covalent organic framework material prepared by using tetraaminophenylmethane and terephthalaldehyde in Example 1.
[0046] Figure 2 This is a physical picture (photo) of the three-dimensional covalent organic framework material prepared in Example 1.
[0047] Figure 3 3D covalent organic framework material prepared in Example 1.
[0048] Figure 4 This is a cross-sectional SEM image corresponding to the covalent organic material composite membrane prepared in Example 1.
[0049] Figure 5 I3 is the covalent organic material composite membrane prepared in Example 1 - (Iodide ion) permeability experimental results, that is, the optical photograph of the three-dimensional covalent organic framework composite membrane blocking polyiodine compounds.
[0050] Figure 6 This is an optical photograph of the adamantane-centered three-dimensional covalent organic framework composite membrane prepared in Example 2 blocking polyiodine compounds.
[0051] Figure 7 This is the charge and discharge cycle performance diagram of the zinc-iodine full battery assembled with the covalent organic material composite membrane prepared in Application Example 1.
[0052] Figure 8 This is the rate performance diagram of the zinc-iodine full battery assembled with the covalent organic material composite membrane prepared in Application Example 1. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0054] The raw materials and consumables used in the following specific implementation methods are all purchased from the market.
[0055] Embodiment 1
[0056] Preparation of three-dimensional covalent organic framework composite membrane:
[0057] The present invention uses tetraaminophenylmethane and terephthalaldehyde to prepare a three-dimensional covalent organic framework material, and its synthesis route is as follows: Figure 1 shown.
[0058] Step 1, add tetraaminophenylmethane (40 mg) and terephthalaldehyde (20 mg) to a reaction tube, add dioxane (1.5 mL) and mesitylene (1.5 mL), ultrasonically disperse at 20-30°C for 15 minutes, add acetic acid solution (3M, 0.1 mL), freeze with liquid nitrogen, flame seal, and heat at 120°C for 72 hours. After cooling to room temperature, filter to obtain a solid powder, wash with anhydrous THF, and vacuum dry at 120°C for 4-8 hours to obtain a yellow three-dimensional covalent organic framework material powder, such as Figure 2 As shown. Further characterization of its XRD results are shown Figure 3 shown.
[0059] Step 2: Disperse 5 mg of the three-dimensional covalent organic framework material powder in step 1 in 40 ml of anhydrous ethanol to obtain a three-dimensional covalent organic framework material liquid; weigh 10 mg of graphene and disperse it in another 40 ml of anhydrous ethanol to obtain a graphene liquid; use a common filtration method to filter the three-dimensional covalent organic framework material liquid and the graphene liquid on a glass fiber diaphragm (base diaphragm) in turn, and dry them to obtain a composite diaphragm. The prepared composite diaphragm was characterized by cross-sectional SEM. Figure 4 The results show that the cross-sectional morphology shows that the material has good consistency.
[0060] Testing of composite diaphragms for I3 in electrolyzers - The inhibitory effect, such as Figure 5 As shown, the left side is 1M ZnSO4+0.1M ZnI2 aqueous solution (simulated I3 - ), the right side is 1M ZnSO4 aqueous solution. The middle is a three-dimensional covalent organic framework composite membrane. After standing for 6 hours (see Figure 5 ), the aqueous solution on the right is still colorless, and the results show that the composite separator has excellent inhibitory effect, laying the foundation for improving battery performance.
[0061] The prepared composite diaphragm was subjected to a full battery cycle performance test, in which adsorbed iodine was used as the positive electrode, zinc foil was used as the negative electrode, and 3M ZnSO4+0.2M ZnI2 aqueous solution was used as the electrolyte. The full battery cycle performance was tested in a battery charge and discharge test instrument. Figure 7 It can be seen that the full battery has 6.5mAh·cm -2 The initial high capacitance at a current density of 20 mA cm -2 , it can still stably cycle for a long time of 800 cycles (1600 hours).
[0062] The prepared composite membrane was tested for full battery rate performance, using adsorbed iodine as the positive electrode, zinc foil as the negative electrode, and 3M ZnSO4+0.2M ZnI2 aqueous solution as the electrolyte. Different current densities were used during the test to test the rate performance of the full battery. Figure 8It can be seen that by -2 At different current densities, the capacity decay is small and can recover to the initial capacity after cycling, indicating good rate performance.
[0063] Example 2
[0064] Preparation of diamond-centered three-dimensional covalent organic framework composite membranes:
[0065] Step 1, add tetraaminophenyladamantane (53 mg) and terephthalaldehyde (20 mg) to a reaction tube, add dioxane (2 mL) and mesitylene (2 mL), ultrasonically disperse at 20-30°C for 20 minutes, add acetic acid solution (3M, 0.15 mL), freeze with liquid nitrogen, flame seal, and heat at 120°C for 120 hours. After cooling to room temperature, filter to obtain a solid powder, extract with anhydrous THF for 24 hours, and vacuum dry at 120°C for 4-8 hours to obtain a yellow adamantane-centered three-dimensional covalent organic framework material powder.
[0066] Step 2: Disperse 5 mg of the adamantane three-dimensional covalent organic framework material powder in step 1 in 40 ml of anhydrous ethanol to obtain adamantane three-dimensional covalent organic framework material liquid; weigh 10 mg of graphene and disperse it in another 40 ml of anhydrous ethanol to obtain a graphene liquid; and filter the adamantane three-dimensional covalent organic framework material liquid and the graphene liquid sequentially on a glass fiber diaphragm (base diaphragm) by suction filtration. Dry and set aside.
[0067] Testing of diamond-based 3D covalent organic framework separators for I3 in electrolyzers - The inhibitory effect of the three-dimensional covalent organic framework membrane of diamond on polyiodine polymer was tested under static conditions.
[0068] The prepared adamantane three-dimensional covalent organic framework separator was subjected to a full battery cycle performance test, in which adsorbed iodine was used as the positive electrode, zinc foil as the negative electrode, and ZnSO4 and ZnI2 aqueous solutions as the electrolyte to test the full battery cycle performance in a battery charge and discharge test instrument.
[0069] The prepared adamantane three-dimensional covalent organic framework separator was subjected to a full-cell rate performance test. Similarly, adsorbed iodine was used as the positive electrode, zinc foil as the negative electrode, and ZnSO4 and ZnI2 aqueous solutions as the electrolyte to test the rate performance of the full cell at different current densities.
[0070] The results are as follows Figure 6As shown, after standing for 6 hours, the zinc sulfate solution on the right side of the H electrolytic cell became colorless. The results showed that the three-dimensional covalent organic framework composite membrane with adamantane as the center also has excellent inhibition effect on polyiodine compounds.
[0071] Comparative Example
[0072] On the basis of Example 1, different aldehyde and amine monomers are selected and combined to obtain different three-dimensional organic framework materials.
[0073] Comparative Group 1: Synthesis of three-dimensional organic materials with carbon-centered 4-aminophenylmethane and terephthalaldehyde. The obtained materials have smaller pores due to short chain connections, which is not conducive to Zn 2+ Pass quickly.
[0074] Comparative Group 2: Carbon-centered 4-aminophenylmethane and p-2,5-diethoxyphthalaldehyde were used to synthesize three-dimensional organic materials. The resulting materials had a smaller specific surface area due to the modification of the side chains, which was not conducive to the performance of the battery.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional covalent organic framework zinc-iodine battery separator, characterized in that: The following steps are involved: (1) tetraaminophenylmethane and terephthalaldehyde ligand are placed in an organic solvent and ultrasonically dispersed to obtain a mixed solution; (2) adding a catalyst to the mixed solution of step (1), heating the solution to react, cooling the solution after the reaction, filtering the solution to obtain a solid powder, washing and purifying the solid powder, and drying the solid powder to obtain an organic framework material; (3) The organic framework material prepared in step (2) and the conductive material are layered and assembled on the base membrane to obtain a three-dimensional covalent organic framework zinc-iodine battery membrane.
2. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to claim 1, characterized in that: In step (1), the terephthalaldehyde ligand is one or more of 2-hydroxyterephthalaldehyde, 2.5-dihydroxyterephthalaldehyde, 2.5-diethoxyterephthalaldehyde, and 2.5-dimethoxyterephthalaldehyde; the molar ratio of the tetraaminophenylmethane to the terephthalaldehyde ligand is 1:1.5-2.5; and the organic solvent is one or more of 1,4-dioxane, mesitylene, o-dichlorobenzene, and n-butanol.
3. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to claim 1, characterized in that: Step (2), the catalyst is 3-9 mol / L acetic acid solution; The volume ratio of the organic solvent in step (1) to the catalyst in step (2) is 3-5:0.1-0.2; Step (2), heating the reaction temperature to 90-120°C, and the reaction time to 70-90h; Step (2), the washing and purification uses a solvent of at least one of tetrahydrofuran, methanol, ethyl acetate, and 1,4-dioxane; In step (2), the drying is performed by vacuum drying at a temperature of 90-130° C. and a drying time of 4-8 h.
4. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to claim 1, characterized in that: In step (3), the conductive material is one or more of graphene, ketjen black, carbon black, and acetylene black; the pore size of the base membrane is 1-5 μm, and the base membrane is any one of a glass fiber membrane, a polyethylene membrane, and a polypropylene membrane.
5. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to claim 1, characterized in that: The specific steps of step (3) are: dispersing the organic framework material in ethanol, the mass volume ratio of the organic framework material to the ethanol is 4-6mg:30-50ml, to obtain an organic framework material liquid; then dispersing the conductive material in another part of the ethanol, the mass volume ratio of the conductive material to the ethanol is 8-12mg:30-50ml, to obtain a conductive material liquid; using a suction filtration method, the organic framework material liquid and the conductive material liquid are sequentially suction-filtered onto the base diaphragm to prepare a zinc-iodine battery diaphragm.
6. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to claim 1, characterized in that: The zinc-iodine battery separator has a thickness of 15-20 mm, and a natural thickness before assembly of 800-1000 μm.
7. The method for preparing the zinc-iodine battery separator of the three-dimensional covalent organic framework according to any one of claims 1 to 6, characterized in that: The tetraaminophenylmethane is replaced by adamantane.
8. A three-dimensional covalent organic framework zinc-iodine battery separator, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. A zinc-iodine battery, characterized in that: The zinc-iodine battery comprises a positive electrode, a negative electrode, an electrolyte and the zinc-iodine battery separator according to claim 8.
10. The zinc-iodine battery according to claim 9, characterized in that: The positive electrode is made of carbon material, a binder is added, and a slurry is prepared, and iodine is adsorbed to make the positive electrode. The carbon material is one or more of microporous carbon, coconut shell carbon or activated carbon, and the binder is one or more of polyvinylidene fluoride, polytetrafluoroethylene, and polyaniline; The negative electrode is a negative electrode of metal zinc foil or other metal alloy containing zinc; The electrolyte is a zinc salt aqueous solution, and the electrolyte consists of 2-5 mol / L ZnSO4 and 0.1-0.3 mol / L ZnI2 aqueous solutions.
Citation Information
Patent Citations
Composite diaphragm for lithium-selenium battery and preparation method of composite diaphragm
CN104638219A
Covalent organic framework film material for removing triclosan in environmental water as well as preparation method and application of same
CN111647184A
Zinc-iodine battery diaphragm based on covalent organic framework as well as preparation method and application of zinc-iodine battery diaphragm
CN115693022A
Electrode material, preparation method thereof and zinc-iodine battery
CN117327241A
Method for producing functional rice cake using safflower leaves
KR102373966B1